Unzipping single DNA molecules to study nucleosome structure and dynamics - Li, Ming (Methods Enzymol, 2012)
DNA-unzipping is a powerful tool to study protein-DNA interactions at the single-molecule level. In this chapter, we provide a detailed and practical guide to performing this technique with an optical trap, using nucleosome studies as an example. We detail protocols for preparing an unzipping template, constructing and calibrating the instrument, and acquiring, processing and analyzing unzipping data. We also summarize major results from utilization of this technique for the studies of nucleosome structure, dynamics, positioning and remodeling.